The variability of the hydrological fronts in the Peru-Chilean region using SST satellite data - Ju. V. Artamonov; E. A. Skripaleva (Ukrainian Antarctic Journal, 2006)
The seasonal and interannual variability of the large-scale fronts in the Peru-Chilean region of Pacific Ocean are investigated, based on SST satellite observations during 1985-2002. Shown, that in climatic seasonal cycle in the equatorial zone Front of North branch of South Equatorial Current is intensifying in second half-year. The fronts of tropical and moderate zones (South Tropical, South branch of South Subequatorial front, South Subtropical and Subantarctic fronts) are intensified, predominantly, in first half-year. The essential interannual variations of front's characteristics have discovered. The anomalous changes of front's intensity to be observed during El Niño events. The latitude position of fronts can to change from year to year by 300-400 km, front's temperature range by 2-3 degrees and front's intensity by 0.6-0.8°С/54 km. It is found, that correlation between interannual anomalies of front's characteristics, anomalies of the areas of Pacific warm equatorial water and index SOI can to equal 0.7-0.8.